Antimicrobial Resistance in Enterobacterales Recovered from Urinary Tract Infections in France - Eric Farfour; Laurent Dortet; Thomas Guillard; Nicolas Chatelain; Agathe Poisson; Assaf Mizrahi; Damien Fournier; Rémy A. Bonnin; Nicolas Degand; Philippe Morand; Frédéric Janvier; Vincent Fihman; et al. (Pathogens, 2022)
In the context of increasing antimicrobial resistance in Enterobacterales, the management of these UTIs has become challenging. We retrospectively assess the prevalence of antimicrobial resistance in Enterobacterales isolates recovered from urinary tract samples in France, between 1 September 2017, to 31 August 2018. Twenty-six French clinical laboratories provided the susceptibility of 134,162 Enterobacterales isolates to 17 antimicrobials. The most frequent species were E. coli (72.0%), Klebsiella pneumoniae (9.7%), Proteus mirabilis (5.8%), and Enterobacter cloacae complex (2.9%). The overall rate of ESBL-producing Enterobacterales was 6.7%, and ranged from 1.0% in P. mirabilis to 19.5% in K. pneumoniae, and from 3.1% in outpatients to 13.6% in long-term care facilities. Overall, 4.1%, 9.3% and 10.5% of the isolates were resistant to cefoxitin, temocillin and pivmecillinam. Cotrimoxazole was the less active compound with 23.4% resistance. Conversely, 4.4%, 12.9%, and 14.3% of the strains were resistant to fosfomycin, nitrofurantoin, and ciprofloxacin. However, less than 1% of E. coli was resistant to fosfomycin and nitrofurantoin. We identified several trends in antibiotics resistances among Enterobacterales isolates recovered from the urinary tract samples in France. Carbapenem-sparing drugs, such as temocillin, mecillinam, fosfomycin, cefoxitin, and nitrofurantoin, remained highly active, including towards ESBL-E.